PENGARUH CAMPUR KODE DALAM PRESENTASI SISWA KELAS VII TERHADAP KEPERCAYAAN DIRI DAN KETERAMPILAN BERBICARA FORMAL - Ahmad Sopyan; Ricky Sukandar; Agus Suryana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was conducted to analyze the influence on code-mixing in seventh-grade students' presentations on their self-confidence and formal speaking skills. The study utilized a quantitative methodology that incorporated a survey technique. The sample included all seventh-grade students, while the sample was selected through chosen via intentional sampling. Information was gathered through questionnaires to measure the level of code-mixing and students' self-confidence, as well as an assessment rubric to evaluate formal speaking skills during presentations. The information was examined through both descriptive and inferential statistical methods to determine the association and influence among the variables. The findings indicate that code-mixing in classroom presentations affects students' self-confidence and formal speaking skills. Excessive code-mixing tends to reduce the quality of formal speech, whereas controlled use of code-mixing can help students express their ideas more confidently. Therefore, teachers should guide students to use proper Indonesian in formal situations while maintaining their self-confidence in public speaking.